Transcriptional Down-Regulation of Major Histocompatibility Complex as a Possible Pathogenesis for Meniere's Disease - Choi, Kwang-Dong; Oh, Eun Hye; Kim, Hyun Sung; Kim, Hyang-Sook; Park, Ji-Yun; Choi, Seo Young; Choi, Jae-Hwan (Frontiers in Neurology, 2022)
Objectives: This study aimed to determine the underlying pathogenesis of Meniere’s disease (MD) using transcriptome analysis. Methods: Total RNA was extracted from the peripheral blood mononuclear cells of 39 patients with MD and 39 controls. Through microarray analysis for nine patients and controls, the differentially expressed genes (DEGs) of those two groups were screened based on cut-off criteria (|fold changes| > 2.0 and adjusted p-value < 0.05). Functional enrichment analysis of DEGs was performed using Gene Ontology. Results: There were 996 DEGs identified in the MD group: 415 were up-regulated and 581 were down-regulated. Functional enrichment analysis indicated that the down-regulated DEGs were significantly enriched in terms related to immune system processes. Among them, 17 genes were enriched in terms for MHC protein complex, and the relative mRNA levels of three markedly down-regulated DEGs (fold changes < -5: HLA-DMA, HLA-DRB1, HLA-DPB1) were significantly decreased in another 30 patients with MD compared to normal controls by quantitative reverse transcription-polymerase chain reaction. However, there were no correlations between the expression levels of these three genes and clinical data including age, onset age, time course, or hearing threshold. Conclusions: Our transcriptome analysis showed that the down-regulated DEGs in MD were mainly associated with the immune system pathways including the MHC protein complex in MD. Remarkably, a breakdown in immunological tolerance mediated by MHC class II may contribute to MD development, which has implications for targeted treatment.